2003
DOI: 10.1074/jbc.m303114200
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Nuclear Localization of Apoptin for Tumor-specific Induction of Apoptosis

Abstract: The chicken anemia virus-derived protein Apoptin induces apoptosis specifically in human tumor and transformed cells and not in normal, untransformed cells. The cell killing activity correlates with a predominantly nuclear localization of Apoptin in tumor cells, whereas in normal cells, it is detected mainly in cytoplasmic structures. To explore the role of nuclear localization for Apoptin-induced cell death in tumor cells, we employed a mutagenesis strategy. First, we demonstrated that the C terminus of Apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(176 citation statements)
references
References 38 publications
5
170
1
Order By: Relevance
“…Mutation of a specific part of Apoptin resulted in a strongly reduced binding and delayed apoptosis. Recently, we have shown that Apoptin contains two different domains that induce apoptosis independently, 13 which might explain why we only observed a delayed apoptosis induction when the DEDAF/Apoptin interaction was prevented. DEDAF was isolated earlier in a yeast twohybrid screen, using the DED of pro-caspases 8 and 10, 16 and was also found by others as a binding partner for the transcription factor E4TF1/hGABP and named YEAF1.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Mutation of a specific part of Apoptin resulted in a strongly reduced binding and delayed apoptosis. Recently, we have shown that Apoptin contains two different domains that induce apoptosis independently, 13 which might explain why we only observed a delayed apoptosis induction when the DEDAF/Apoptin interaction was prevented. DEDAF was isolated earlier in a yeast twohybrid screen, using the DED of pro-caspases 8 and 10, 16 and was also found by others as a binding partner for the transcription factor E4TF1/hGABP and named YEAF1.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, we have shown that inhibitors of transcription or translation do not affect Apoptin's activity; however, this does not exclude a function in transcriptional repression. 13 Overexpression of DEDAF induced apoptosis in three different tumor cell lines, but not in normal fibroblasts or mesenchymal stem cells. In contrast, FADD overexpression did induce apoptosis in these normal cells, indicating that the cells were competent to execute apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The subcellular localization of apoptin appears to be important for the selective toxicity towards transformed and cancer cells. In cells resistant to apoptin-mediated cell death, the protein has a cytoplasmic localization, whereas in sensitive cells, apoptin is found in the nucleus (Danen-Van Oorschot et al, 2003). Apoptin was described to be specifically phosphorylated in transformed cells by an unknown kinase, which was proposed to be important for the nuclear localization and apoptotic activity of apoptin (Rohn et al, 2002).…”
mentioning
confidence: 99%